Novel volumetric modulated arc therapy approach for lattice radiation therapy for bulky liver tumors - Chung, Christine V.; Nair, Saurabh S.; Khan, Meena S.; Nguyen, Callistus I.; Martin-Paulpeter, Rachael M.; Ludmir, Ethan B.; Court, Laurence E.; Niedzielski, Joshua S. (Frontiers in Oncology, 2025)
PurposeLattice radiation therapy (LRT) is a type of spatially fractionated radiation therapy that has emerged as an effective treatment approach for bulky solid tumors. RapidArc Dynamic (RAD) is a novel beam delivery approach that may be advantageous for LRT. The purpose of this in silico study was to evaluate and compare a novel RAD-based LRT approach (RAD-LRT) with conventional volumetric modulated arc therapy (VMAT)-based LRT (VMAT-LRT).MethodsTwenty patients with bulky liver tumors treated with RT were retrospectively identified. VMAT-LRT and RAD-LRT plans were generated for all patients. Lattice spheres were placed in a standardized hexagonal pattern with alternating high-dose spheres (vertex tumor volume high [VTVH], analogous to the peak dose) and low-dose control spheres (vertex tumor volume low [VTVL], analogous to the valley dose). Gross tumor volumes (GTVs)<1,000 cm3 and GTVs ≥1,000 cm3 were planned with 1.0-cm-diameter spheres (n=10) and 1.5-cm-diameter sphere (n=10), respectively. A prescription dose of 20 Gy to 80% of the VTVH was utilized. LRT dose metrics (e.g., peak-to-valley dose ratios, VTVH D80, VTVL Dmean) were calculated and were compared using paired Wilcoxon sign-ranked test. Planning efficiency was assessed by evaluating planning structures, planning time, and number of treatment fields.ResultsFor all 20 cases, RAD-LRT achieved superior plan quality than VMAT-LRT, indicated by similar prescription dose coverage (group mean, VTVH D80: 20.40 Gy for VMAT-LRT, 20.50 Gy for RAD-LRT) but significantly lower valley dose (group mean, VTVL mean dose: 3.40 Gy for VMAT-LRT, 2.20 Gy for RAD-LRT, p<0.0001). Compared to VMAT-LRT, RAD-LRT required fewer planning structures (mean ± SD, 9 ± 1 for VMAT-LRT, 4 ± 1 for RAD-LRT), less planning time (26 ± 8 min for VMAT-LRT, 18 ± 11 min for RAD-LRT), and fewer treatment beams (5 ± 1 arcs for VMAT-LRT, 1 arc with 4 ± 1 static ports for RAD-LRT). RAD-LRT also had significantly higher peak-to-valley dose ratios (group mean, VTVH/VTVL D90 ratio: 8.92 for VMAT-LRT, 18.20 for RAD-LRT, p<0.0001).ConclusionRAD may offer a unique approach to Lattice RT. RAD-LRT generated high quality plans with notable treatment planning efficiency, allowing for creation of quality plans without extensive planning time and LRT expertise.